Processo de apoio para análise de informações em inteligência competitiva com foco em inovação - Côrtes, Ariane Marcela (2013)
This dissertion's main purpose is to characterize a process of data analysis for competitive intelligence for strategic decisions in innovation. Today, we’re facing a problem that is not related to information access, but its use after being analyzed to support decision making. The information analysis stage of the cycle of competitive intelligence is critical, since it is here that the information will be transformed into intelligence.This is an applied research, descriptive and qualitative. Regarding the use of techniques, is bibliographic to collect secondary data and applied questionnaires and interviews to collect primary data. The sample was non-probabilistic and intentional. Questionnaires were sent to 34 consultants of Núcleos de Apoio à Gestão da Inovação of Paraná. 13 responded the questionnaire and 3 participated the interview. As results, there is a sequence of the techniques used and the profile of analysts, including their graduation, time of experience and skills that they have more and that they have less. Regarding the analysis of information for innovation, a survey was made about what are differences between it and the analysis for decisions not focused on innovation and listed the characteristics of a process analysis focused innovation.